Photodynamic therapy - A strategic review - Malik Rajvir; Manocha Anish; Suresh D (Wolters Kluwer Medknow Publications, 2010)
Mechanical removal of the biofilm and adjunctive use of antibacterial disinfectants or various antibiotics have been conventional methods of the periodontitis therapy. There has been an upsurge of bacterial strains becoming resistant due to the injudicious use of antibiotics, recently. As a result there is pronounced interest and keenness in the development of alternate antimicrobial concepts. As the scientific community seeks alternatives to antibiotic treatment, periodontal researchers have found that photodynamic therapy (PDT) is advantageous to suppress anaerobic bacteria. Hence, PDT could be an alternative to conventional periodontal therapeutic methods. This review elucidates the evolution and use of photo dynamic therapy. The application of photosensitizing dyes and their excitation by visible light enables effective killing of periodontopathogens. Even though PDT is still in the experimental stages of development and testing, the method may be an adjunct to conventional antibacterial measures in periodontology. PDT application has an adjunctive benefit besides mechanical treatment at sites with difficult access. Necessity for flap operations may be reduced, patient comfort may increase and treatment time decrease. Clinical follow-up studies are needed to confirm the efficacy of the procedure.